The Otto Aufranc Award: Modifiable versus Nonmodifiable Risk Factors for Infection After Hip Arthroplasty. Issue 2 (February 2015) - Maoz, Guy; Phillips, Michael; Bosco, Joseph; Slover, James; Stachel, Anna; Inneh, Ifeoma; Iorio, Richard
Abstract: Background: Periprosthetic joint infections (PJIs) are associated with increased morbidity and cost. It would be important to identify any modifiable patient‐ and surgical‐related factors that could be modified before surgery to decrease the risk of PJI. Questions/purposes: We sought to identify and quantify the magnitude of modifiable risk factors for deep PJIs after primary hip arthroplasty. Methods: A series of 3672 primary and 406 revision hip arthroplasties performed at a single specialty hospital over a 3‐year period were reviewed. All deep PJIs were identified using the Centers for Disease Control and Prevention case definitions (ie, occurs within 30‐90 days postoperatively, involves deep soft tissues of the incision, purulent drainage, dehiscence and fever, localized pain or tenderness). Univariate and multivariate analyses determined the association between patient and surgical risk factors and PJIs. For the elective patients, the procedure was performed on the day of admission ("same‐day procedure"), whereas for the fracture and nonelective patients, the procedure was performed 1 or more days postadmission ("nonsame‐day procedure"). Staphylococcus aureus colonization, tobacco use, and body mass index (BMI) were defined as patient‐related modifiable risk factors. Results: Forty‐seven (1.3%) deep PJIs were identified. Infection developed in 20 of 363 hips of nonsame‐day procedures and 27 of 3309 same‐day procedures (p = 0.006). There were eight (2%) infections in the revision group. After controlling for confounding variables, our multivariate analysis showed that BMI ≧ 40 kg/m 2 (odds ratio [OR], 4.13; 95% confidence interval [CI], 1.3‐12.88; p = 0.01), operating time > 115 minutes (OR, 3.38; 95% CI, 1.23‐9.28; p = 0.018), nonsame‐day surgery (OR, 4.16; 95% CI, 1.44‐12.02; p = 0.008), and revision surgery (OR, 4.23; 95% CI, 1.67‐10.72; p < 0.001) are significant risk factors for PJIs. Tobacco use and S aureus colonization were additive risk factors when combined with other significant risk factors (OR, 12.76; 95% CI, 2.47‐66.16; p = 0.017). Conclusions: Nonsame‐day hip and revision arthroplasties have higher infection rates than same‐day primary surgeries. These characteristics are not modifiable and should be categorized as a separate cohort for complication‐reporting purposes. Potentially modifiable risk factors in our patient population include operating time, elevated BMI, tobacco use, and S aureus colonization. Modifying risk factors may decrease the incidence of PJIs. When reporting deep PJI rates, stratification into preventable versus nonpreventable infections may provide a better assessment of performance on an institutional and individual surgeon level. Level of Evidence: Level IV, prognostic study. See Guidelines for Authors for a complete description of levels of evidence.